Fungus Ball in Concha Bullosa: A Rare Case with Anosmia - Mahmut Özkırıs; Zeliha Kapusuz; Selda Seçkın; Levent Saydam (Case Reports in Otolaryngology)
Concha bullosa is the pneumatization of the concha and is one of the most common variations of the sinonasal anatomy. The histopathological changes caused by the infections which arise from the impaired aeration of conchal cavity are frequently found. Fungus ball of the nasal cavity is an extremely rare, fungal infection with only three cases reported previously. In this paper, we present the fourth fungus ball case which developed within a concha bullosa and presented with anosmia.